Functional Grammar and Argumentative Discourse: Emphasis and Emphatic Marking in Arabic (Linguist, 2021)
In earlier work (Moutaouakil 1989)), I argued that within the framework of Functional Grammar (e.g. Dik 1997)` inna-constructions in Standard Modern Arabic (hereafter SMA) be analysed as  focus constructions where (Contrastive)  Focus function is assigned to the predication. In Mackenzie (2009), it is argued that within the FDG framework these constructions should rather be approached in terms of Emphasis.Subscribing to Mackenzie’s view, I here re-examine the interpersonal and structural properties of inna-constructions (together with the other types of emphatic constructions in Arabic) in light of the way in which Emphasis and emphatic marking are described in Hengeveld and Mackenzie (2008). It is believed that the proposals made throughout this study will enrich the FDG approach in the area of argumentative discourse.
Keywords: Functional Grammar; Standard Modern Arabic; argumentative discourse